Enhancing Employee Loyalty Through Work Environment and Social Support with the Mediating Role of Engagement - R. Rudi Alhempi; Saiful Anuar; Rini Elfina; Syahrial Shaddiq (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
This study aims to explore the influence of organizational culture, work environment, and social support on employee loyalty, with employee engagement as a mediating variable. This study uses a quantitative approach with a causal design. Data were collected from 50 employees of PT. XYZ Kerinci through a structured questionnaire, carefully designed to measure employee perceptions of the work environment, organizational socio-cultural support, and engagement. The analysis used Structural Equation Modeling (SEM) based on Partial Least Squares (SmartPLS). The results of the study found that organizational culture and work environment significantly affect employee loyalty through employee engagement, while social support does not show a direct, weak and insignificant effect. Organizational culture with the highest significant value emphasizes the importance of a supportive and value-oriented culture in increasing loyalty, so that good organizational culture and work environment play an important role in increasing employee loyalty through employee engagement. This study provides recommendations for management in designing human resource management strategies that focus on increasing engagement as the key to employee loyalty.